UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN MELALUI PELAKSANAAN SUPERVISI KLINIS TEKNIK KUNJUNGAN KELAS DI SMP NEGERI 6 PALEMBAYAN KABUPATEN AGAM PROVINSI SUMATERA BARAT - Delfian Delfian (Universitas PGRI Sumatera Barat, 2023)
The general objective of this research is to address the challenges faced by teachers in the teaching and learning process. The specific aim of this research is to enhance teachers' ability in utilizing instructional media through clinical supervision activities using the classroom visitation technique at SMP Negeri 6 Palembayan. The research results indicate that the implementation of clinical supervision through classroom visitation techniques has effectively improved teachers' proficiency in using instructional media at SMP Negeri 6 Palembayan. In the first cycle, teachers' ability to design and use instructional media achieved a percentage score of 66.3%, while in the second cycle, a significant improvement was observed with a percentage score of 83.6%. Therefore, it can be concluded that the implementation of clinical supervision through classroom visitation techniques has successfully addressed the challenges and difficulties faced by teachers in designing and using instructional media at SMP Negeri 6 Palembayan.